2022
DOI: 10.1039/d2nj04578h
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline salts of anionic free-base tetrapyrazinoporphyrazines with alkyl-substituents or an extended π-electron system

Abstract: Free-base octamethyltetrapyrazinoporphyrazine (H2TPyzPzMe8), octaethyltetrapyrazonoporphirazine (H2TPyzPzEt8), and tetra-2,3-[5,6-(9,10-phenanthro)pyrazino]porphyrazine (H2T(PhnPyz)Pz) have been synthesized by cyclic tetramerization of corresponding dinitriles followed by demetallation of the obtained magnesium complexes. Reduction or deprotonation of these...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…A good fitting of the experimental data (Figure ) using g (Cu II ) = 2.19 and g = 2.0000 for F 64 Pc •3– yielded J = −0.56 cm –1 . The ligand-only g = 2.0000 value is consistent with g = 2.003–2.009 measured for the solution, ligand-only signal of [Zn­(F 64 Pc •3– )] − . , Compared with F 64 Pc •3– , the intramolecular couplings between Cu II and F x Pc •3– , x = 8 and 16, namely, −10.8 and −5.6 cm –1 , respectively (Table ) are at least 1 order of magnitude larger. , As the degree of fluorination increases, the intramolecular magnetic coupling decreases, a trend consistent with the notion of enhanced spin density transfer to acceptor fluoro-substituents as x increases. Thus, the weakest coupling in [Cu II (F 64 Pc) •3– ] − could be explained by the extreme electron deficiency of its Pc core. , The geometry around the copper­(II) atoms most probably does not affected the J values since, according to the SHAPE 2.1, estimation, for all three anions with x = 8, 16, and 64, the geometry of copper­(II) is very close to square-planar, D 4 h symmetry.…”
Section: Magnetic Interactions and F Effectssupporting
confidence: 81%
See 3 more Smart Citations
“…A good fitting of the experimental data (Figure ) using g (Cu II ) = 2.19 and g = 2.0000 for F 64 Pc •3– yielded J = −0.56 cm –1 . The ligand-only g = 2.0000 value is consistent with g = 2.003–2.009 measured for the solution, ligand-only signal of [Zn­(F 64 Pc •3– )] − . , Compared with F 64 Pc •3– , the intramolecular couplings between Cu II and F x Pc •3– , x = 8 and 16, namely, −10.8 and −5.6 cm –1 , respectively (Table ) are at least 1 order of magnitude larger. , As the degree of fluorination increases, the intramolecular magnetic coupling decreases, a trend consistent with the notion of enhanced spin density transfer to acceptor fluoro-substituents as x increases. Thus, the weakest coupling in [Cu II (F 64 Pc) •3– ] − could be explained by the extreme electron deficiency of its Pc core. , The geometry around the copper­(II) atoms most probably does not affected the J values since, according to the SHAPE 2.1, estimation, for all three anions with x = 8, 16, and 64, the geometry of copper­(II) is very close to square-planar, D 4 h symmetry.…”
Section: Magnetic Interactions and F Effectssupporting
confidence: 81%
“…The ligand-only g = 2.0000 value is consistent with g = 2.003–2.009 measured for the solution, ligand-only signal of [Zn(F 64 Pc •3– )] − . 16 , 44 Compared with F 64 Pc •3– , the intramolecular couplings between Cu II and F x Pc •3– , x = 8 and 16, namely, −10.8 and −5.6 cm –1 , respectively ( Table 4 ) are at least 1 order of magnitude larger. 28 , 29 As the degree of fluorination increases, the intramolecular magnetic coupling decreases, a trend consistent with the notion of enhanced spin density transfer to acceptor fluoro-substituents as x increases.…”
Section: Magnetic Interactions and F Effectsmentioning
confidence: 95%
See 2 more Smart Citations
“…[7][8][9] Compounds based on reduced phthalocyanines and related derivatives have also been extensively studied since they can potentially form compounds with coupling of spins. [10][11][12][13][14][15][16][17][18][19][20][21] Among such macrocycles vanadium complexes are interesting primarily due to the presence of an axial ligand, which promotes stacking in crystals, and paramagnetic properties of the central metal. [14][15][16][17][18] Hadt and colleagues have shown that vanadyl phthalocyanine, when mixed with titanyl phthalocyanine, and copper phthalocyanine mixed with zinc phthalocyanine, are potential options for use in quantum computing.…”
Section: Introductionmentioning
confidence: 99%